Medical Microbiology (De Gruyter Textbook, 2022)
Medical Microbiology is an excellent and easy-to-use textbook which explains the roles of microorganisms in human health and illness. Written in a clear and engaging manner, the book provides an overview of pathogenic organisms, their diagnosis and treatment tools as well as the molecular mechanisms of hostpathogen interactions and antimicrobial drug resistance.